Temporal Bone Adenoma: A Comprehensive Analysis of Clinical Aspects and Surgical Outcome on a Very Rare Entity - Alsalman, Hussain; Crowther, John A.; McLellan, Douglas; Kontorinis, Georgios (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The aim of this study is to present our experience in dealing with middle ear adenomas (MEAs), very rare tumors of the middle ear.Methods The medical notes of individuals with MEAs treated in tertiary referral; academic settings were retrospectively reviewed. We recorded the presenting symptoms, imaging findings, and pathology results. We additionally examined our surgical outcomes, follow-up period, recurrence, and morbidity.Results We identified four patients with MEAs: two males and two females with an average age of 36.25 years (range = 27–51 years). Despite the detailed imaging studies, including computed tomography and magnetic resonance imaging with intravenous contrast administration, a biopsy was essential in setting the diagnosis. Total surgical resection was achieved in all patients without any recurrence over an average of 6 years (range = 3–10 years). Complete ipsilateral deafness was the commonest surgical morbidity due to footplate infiltration by the tumor.Conclusion Total surgical resection is the treatment of choice in MEAs to minimize the risk for recurrence; this can come with morbidity, mostly sensorineural deafness. Given the very limited literature, long-term follow-up is recommended.
Keywords: adenoma; facial nerve; mastoid; middle ear tumor